2015
DOI: 10.4081/oncol.2015.274
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for non-Hodgkin’s lymphoma

Abstract: Non-Hodgkin lymphomas (NHLs) are a diverse group of blood cancers derived from lymphocytes that vary significantly in their severity. Surgery is not often used as a treatment because of the efficacy of chemotherapy, biological therapy, radiotherapy and hematopoietic stem cell transplantation. We reviewed the natural history and possible role of surgery for NHL. Surgery may be useful in confirming or refuting an equivocal radiological diagnosis through biopsy, removing symptomatic limited disease from an affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…An elective laparoscopic splenectomy can be performed in patients with non Hodkin lymphoma for acquiring a histological diagnosis. In fact, a pathologic analysis of spleen tissue is considered to be the gold standard for non-Hodgkin lymphomas and additionally it is not necessary for the spleen to be removed intact[ 27 ]. It is doubtful though, whether a splenectomy is worthwhile in this case, as it may delay the curative chemotherapy[ 28 ].…”
Section: Indicationsmentioning
confidence: 99%
“…An elective laparoscopic splenectomy can be performed in patients with non Hodkin lymphoma for acquiring a histological diagnosis. In fact, a pathologic analysis of spleen tissue is considered to be the gold standard for non-Hodgkin lymphomas and additionally it is not necessary for the spleen to be removed intact[ 27 ]. It is doubtful though, whether a splenectomy is worthwhile in this case, as it may delay the curative chemotherapy[ 28 ].…”
Section: Indicationsmentioning
confidence: 99%
“…While the role of surgery in the treatment of gastrointestinal lymphoma is debatable, performing surgery may provide invaluable prognostic information, including extensiveness of the tumor and its' stage. Two definitive indications for surgery exist in patients with cecal lymphoma: obstruction and perforation [19]. O. Bairey et al showed the rate of spontaneous perforation was high (5 out of 17 patients), he recommended to perform elective hemicolectomy to prevent such complication [7].…”
Section: Discussionmentioning
confidence: 99%
“…These patients would be better managed with chemotherapy, radiotherapy or immunotherapy [2, 3]. Surgery plays a minor role in selected patients with non-Hodgkin's lymphoma [4]. Nodal non-Hodgkin's lymphoma has been associated with HIV infection.…”
Section: Introductionmentioning
confidence: 99%